Design of energy‐efficient ternary circuits using differential cascode voltage switch strategies in carbon nanotube field effect transistor technology. Issue 7 (27th October 2020) - Sharma, Trapti; Kumre, Laxmi
Abstract : Differential cascode voltage switch (DCVS) is a static technique which offers the advantages of layout density, logic flexibility together with improved delay and power consumption. In this study, DCVS‐based ternary logic gates and unary operators are reported using static diode voltage divider topology. The main focus of the proposed ternary designs using DCVS logic style is to provide minimum energy consumption with less area overhead. In the presented method, a new power efficient and compact solution is being provided to improve the driving capability of the ternary DCVS circuits. All the simulations are performed on HSPICE synopsis simulator using 32 nm technology under different operational conditions. For the inversion and logical operations, the proposed method has a maximum power reduction of 45% and an energy reduction of 30% as compared to earlier reported DCVS designs. In the case of shifting operators, the maximum power reduction of 38.93% and an energy reduction of 39% are achieved. The design performance is robust when subjected to various process variation effects and have sufficient noise margins.